Pré-decisão em políticas públicas: a entrada da temática da inclusão digital na agenda do Governo do Estado de São Paulo - Amaro, Natanael Benedito (2012)
The goal of this dissertation is to examine how the issue of digital inclusion agenda entered the government of São Paulo and how designed the digital inclusion program Acessa Sao Paulo. By studying this policy, we sought to identify who were the people who discussed this issue, why they did it, it how done, who participated, finally get behind the scenes of these discussions that preceded the conception of this public policy. To find the relevant actors who participated in the design of public policy of digital inclusion in São Paulo’s, state there was realized a literature getting up about the subject and several contacts were made by e-mail and / or social networks, seeking names of those who participated in this discussions that leading the deployment of digital inclusion program at São Paulo’s state. Before the confirmation of the involvement of those actors, there was made an invitation to them participate in the work through an interview. The entry of the issue of digital inclusion was a slow and gradual process that started since the take office of Governor Mário Covas for his first mandate (1995-1998). The use of computerization by the government was in it’s foressen government’ plane in 1994 as a way to modernize the administrative machine and bring near the state citizens. The need to create a digital inclusion program for low-income citizens would have access to the internet should, above all, the e-government initiatives promoted by the State that was by intent to deliver public services to citizens through internet. At the beginning of the 2000’s internet access was a privilege for few. Hence that, the need to think in a policy that promote the digital inclusion of these people. That was the main reason for the government to assume that the issue of digital inclusion was a problem to be solved. And definitively entered at the government's agenda and subsequently giving rise to Acessa São Paulo.